Perancangan Animasi 2D Mengenai Upaya Pencegahan Penyakit Saat Musim Hujan - Ikmaludin (Shofanah Media Berkah, 2023)
The high cases of disease spread during the rainy season must be overcome quickly and in various ways. A lot of socialization has been carried out, but it has not been spread evenly. Therefore, the design of this animation helps to spread information quickly and easily. Design is the activity of compiling the manufacture of a product from the initial idea to the final product. This animation design uses 3 stages, namely pre-production, production, and post-production. Pre-production is done by collecting and analyzing data, creating concepts, scripts, and storyboards, designing characters, properties, and environments. Meanwhile, the production is conducted through layout, animation, dubbing & sound effects, and compositing. Finally, post-production is conducted through editing, rendering, and publishing. The results of this animation design are animations that describe the symptoms of disease and disease prevention efforts during the rainy season. This animation has a duration of about 3 minutes in an mp4 format. This animation was published on the youtube channel.